Analisis Peran Stakeholder Desa Wisata Carangsari, Kecamatan Petang, Kabupaten Badung - Cahyana, Shafa Raya; Nugroho, Saptono (JURNAL DESTINASI PARIWISATA, 2019)
Carangsari tourism Village is one of the tourist villages in Badung Regency, with various natural and cultural potentials. This study aims to determine the role of the three pillars of tourism in carrying out its right and responsibilitiestowards of Carangsari Tourism Village.The metode used in this study is a qualitative method with qualitative descriptive techniques understand the role of stakeholders in Carangsari Tourism Village, Petang District, Badung Regency. Used some sources of data including primary data and secondary data. The collection data technique, in this study, is using observation, interviews, library studies, and several interviewguidance instrument. Determination of informant in the study of the role of stakeholder in Carangsari Tourism Village used purposive sampling to obtain accurate data on the role of three tourism pillar actor on management in Carangsari Tourism Village, Petang District, Badung Regency. The results of this study obtained the active aspectf, status, right, and obligation Carangsari Tourism Village, Petang District, Badung Regency.Keywords: Stakeholder, Role, Village Tourism, and Badung.